Does concurrent self-administered transcranial direct current stimulation and attention bias modification training improve symptoms of binge eating disorder? Protocol for the TANDEM feasibility randomized controlled trial - Flynn, Michaela; Campbell, Iain; Schmidt, Ulrike (Frontiers in Psychiatry, 2022)
Background: Binge eating disorder (BED) is a common and disabling problem associated with impaired cognitive control. Preliminary studies show that brain-directed treatments, including transcranial direct current stimulation (tDCS) and attention bias modification training (ABMT), improve cognitive control and alleviate symptoms of BED. When combined, tDCS may enhance the effects of ABMT, and vice versa, thereby improving treatment outcomes. Methods: This protocol describes a feasibility single-blind randomised control trial of concurrent self-administered tDCS and ABMT in adults with BED (The TANDEM Trial). Eighty adults with BED will be randomly assigned to one of four groups: ABMT with real or sham self-administered tDCS, ABMT only, or waiting list control. In the treatment arms, participants will complete 10-sessions of their allocated intervention over 2-3 weeks. Outcomes will be assessed at baseline (T0), 3-weeks post randomisation (T1), and 8 weeks post randomisation (T2). Feasibility will be evaluated by assessing recruitment/retention rates and blinding success. Acceptability will be assessed quantitatively via participant ratings and qualitatively via semi-structured interviews. Binge frequency (i.e., change in monthly binge episodes from pre-treatment to follow-up) will be the primary clinical outcome and rate ratios from Poisson regression will be reported. Secondary outcomes will assess changes in ED and general psychopathology, attention bias towards high calorie foods, and executive function. Discussion: It is hoped that data from the trial will contribute to the development of neurobiologically informed treatments for BED, provide insights into the potential use of at-home variants of tDCS, and inform the design of future large scale trials.